Association between blood pressure and circadian timing of physical activity of Japanese workers - Imamura, Momoko; Tahara, Yu; Suiko, Takahiko; Nagamori, Yuki; Shibata, Shigenobu (Frontiers in Physiology, 2022)
High blood pressure (BP) is reported to be accounted for more than 10 million deaths, and the high prevalence of hypertension is a global issue. Exercise is known to reduce BP and the optimal exercise prescription has been discussed. Furthermore, since the circadian clock plays an important role in BP regulation and its related physiological functions, the time-of-day difference in the effect of exercise on BP is suggested. However, when people should regularly exercise for the prevention of hypertension remains unclear. In this cross-sectional research, we analyzed the association of habitual exercise and BP depending on their performed timing, time length, and frequency for three levels of intensity from an analysis of questionnaire answered by Japanese male workers (N = 2,343, mean age ± SE = 49.2 ± 0.2 years old, date: June 2021). From the subjects who responded, subjects with irregularly high or low BP, no regular physical activity or under the treatment of hypertension were excluded from the analysis. From the comparison of SBP and DBP between those who performed physical activity at each time period, vigorous or moderate physical activity in the evening (18:00–21:00) showed significantly lower average BP. On the other hand, those who walked in early morning (03:00–06:00) showed higher DBP. These time-specific differences were confirmed from multiple regression analysis, eliminating the confounding factors such as age and BMI. When participants were divided into groups according to their BP, compared to normal BP groups, higher BP groups exercised less in the evening. Our findings suggest that when to exercise is important, and that exercising in the evening (18:00–21:00) may be better to achieve the hypotensive effect of exercise.